1996
DOI: 10.1097/00007691-199608000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of the Monoethylglycinexylidide Test in Pediatric Liver Transplant Candidates

Abstract: The objective of this prospective study was to assess the prognostic value of dynamic and static liver function tests and clinical symptoms in pediatric patients with chronic end-stage liver disease in a serial examination including three evaluations at 3-month intervals. Of the 24 patients entering the study, six were given transplants within the observation period of 10 months. Of the remaining 18 patients who were considered in the final evaluation, five died before transplantation was possible. The variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…After i.v. administration it has been shown to be a rapid and sensitive indicator of oxidative drug metabolizing hepatic function in liver disease (77)(78)(79)(80)(81)(82)(83) and in pre-and post-transplant conditions (84)(85)(86)(87)(88)(89). Recently, Shiffman et al (90) reported the results of the lidocaine test performed in 225 patients with chronic hepatitis.…”
Section: Lidocaine For 3a4mentioning
confidence: 99%
“…After i.v. administration it has been shown to be a rapid and sensitive indicator of oxidative drug metabolizing hepatic function in liver disease (77)(78)(79)(80)(81)(82)(83) and in pre-and post-transplant conditions (84)(85)(86)(87)(88)(89). Recently, Shiffman et al (90) reported the results of the lidocaine test performed in 225 patients with chronic hepatitis.…”
Section: Lidocaine For 3a4mentioning
confidence: 99%
“…It would be useful to determine the value of the test in evaluating the function of the liver during its various diseases, for the hitherto existing researches [19][20][21] are mainly concentrated on describing, how the test can be used to evaluate the usefulness of the organ for transplantation and to forecast its functions.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the results of the MEGX formation test fairly accurately reflect the severity of hepatic dysfunction, making it valuable both for quantitative evaluation of liver function and as a prognostic tool in adults with liver disease ( 96). Moreover, liver function tests have recently been used as indices of the status of restoration of hepatic drug‐oxidizing capacity in liver transplantation patients ( 100–106). As stated above, the metabolism of drugs whose biotransformation is mediated by this CYP has been reported to be inhibited (30–50%) in liver disease (cirrhosis) ( 80–91).…”
Section: Cyp3amentioning
confidence: 99%